Individual Characteristics That Promote or Prevent Psychological Safety and Error Reporting in Healthcare: A Systematic Review - Wawersik DM; Boutin Jr ER; Gore T; Palaganas JC (Dove Medical Press, 2023)
Dawn M Wawersik,1,2 Emile R Boutin Jr,1 Teresa Gore,3 Janice C Palaganas1,4 1MGH Institute of Health Professions, Boston, MA, USA; 2Henry Ford College, Dearborn, MI, USA; 3Nova Southeastern University, Fort Lauderdale, FL, USA; 4Harvard Medical School, Boston, MA, USACorrespondence: Dawn M Wawersik, Email dwawersi@nova.eduBackground: Healthcare errors continue to be a safety issue and an economic burden that causes death, increased length of stays, and emotional trauma to families and the person who commits the error.  Speaking up and error reporting within a safety culture can reduce the incidence of error; however, this is complex and multifaceted.Aim: This systematic review investigates individual characteristics that support or prevent speaking up behaviors when adverse events occur.  This study further explores how organizational interventions designed to promote error reporting correlate to individual characteristics and perceptions of psychological safety. &#x202FMethods: A systematic review of peer-reviewed articles in healthcare that contain characteristics of an individual that promote or prevent error reporting was conducted. The search yielded 1233 articles published from 2015 to 2021. From this set, 81 full-text articles were assessed for eligibility and ultimately extracted data from 28 articles evaluated for quality using Joanna Briggs Institute critical appraisal tools©.Principal Findings: The primary themes for individual character traits, values, and beliefs that influence a person's decision to speak up/report an error include self-confidence and positive perceptions of self, the organization, and leadership. Education, experience and knowledge are sub themes that relate to confidence. The primary individual characteristics that serve as barriers are 1) self-preservation associated with fear and 2) negative perceptions of self, the organization, and leadership.Conclusion: The results show that an individual's perception of their environment, whether or not it is psychologically safe, may be impacted by personal perceptions that stem from deep-seated personal values. This exposes a crucial need to explore cultural and diversity aspects of healthcare error reporting and how to individualize interventions to reduce fear and promote error reporting.Keywords: speaking up, error reporting, psychological safety, healthcare error, individual characteristics, systematic review